Systematic review and meta-analysis of fear of falling and fall-related efficacy in a widely disseminated community-based fall prevention program. (November 2020) - Yoshikawa, Aya; Ramirez, Gilbert; Smith, Matthew Lee; Lee, Shinduk; Ory, Marcia G.
Highlights: Fear of falling limits activities and increases fall risks. The AMOB/VLL program improved fear of falling and fall-related efficacy. The use of a standard measure is critical for evaluating interventions. Abstract: Background: Fear of falling restricts mobility and increases fall risk among older adults. Fall-related efficacy (i.e. the confidence to perform activities without falling), a construct related to fear of falling, has also been associated with active living and fall prevention. This study statistically synthesized the program effects of A Matter of Balance Volunteer Lay Leader (AMOB/VLL) model, designed to improve fall-related efficacy and promote daily activities among community-dwelling older adults. Methods: Research articles and doctoral dissertations that examined the effect of the AMOB/VLL on fear of falling and fall-related efficacy were searched from multiple databases. A random effects model was used to compute mean weighted effect sizes, 95 % CIs, and heterogeneity (I 2 ). Bias was examined through a funnel plot and Egger's test. Factors associated with heterogeneity were also explored. Results: Seventeen AMOB/VLL studies involving 3, 860 participants were identified. The pooled effects of the 13 studies with sufficient information for effect size calculation, were −0.29 (95 % CI: −0.40, −0.19) for fear of falling and 0.51 (95 % CI: 0.42, 0.60) for fall-related efficacy. Effect sizes differed partially due to outcome measures of fall-related efficacy. Covariate adjustment and study quality were not associated with differences in effect sizes. No substantial evidence of asymmetry and publication bias was found. Conclusion: This study provides evidence supporting AMOB/VLL as an effective intervention for reducing fear of falling and improving fall-related efficacy. A greater consistency in outcome measures is needed to optimally capture changes in fear of falling and fall-related efficacy among community-dwelling older adults.